2018
DOI: 10.1007/s10237-018-1039-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogel injection on borderzone contractility post-myocardial infarction

Abstract: Injectable hydrogels are a potential therapy for mitigating adverse left ventricular (LV) remodeling after myocardial infarction (MI). Previous studies using magnetic resonance imaging (MRI) have shown that hydrogel treatment improves systolic strain in the borderzone (BZ) region surrounding the infarct. However, the corresponding contractile properties of the BZ myocardium are still unknown. The goal of the current study was to quantify the in vivo contractile properties of the BZ myocardium post-MI in an ovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
0
19
2
Order By: Relevance
“…Since injectable hydrogels have proven to be a good treatment in clinical practice (Wang H. et al, 2018) while the method is also encountered with the lack of suitable injectable hydrogel materials owing to the respective characteristics of natural hydrogels or synthetic hydrogels. Therefore, the exploration of clinically appropriate injectable hydrogel materials is also one of the research priorities ( Table 1).…”
Section: Synthetic Hydrogelsmentioning
confidence: 99%
“…Since injectable hydrogels have proven to be a good treatment in clinical practice (Wang H. et al, 2018) while the method is also encountered with the lack of suitable injectable hydrogel materials owing to the respective characteristics of natural hydrogels or synthetic hydrogels. Therefore, the exploration of clinically appropriate injectable hydrogel materials is also one of the research priorities ( Table 1).…”
Section: Synthetic Hydrogelsmentioning
confidence: 99%
“…Echocardiographic examination of the mitral leaflets and left ventricular myocardium was used in early studies to investigate the role of the papillary muscles in mitral valve closure [10,22]. This group previously showed that in-vivo injected shear-thinning biomaterial significantly improved regional contractile function in the border zone and reduced LV remodeling in a cohort of Dorset sheep when compared to untreated controls [33]. The present study uses a similar animal-specific MRI-based FE model to quantify papillary muscle motion before and 8 weeks after MI in the same ovine cohort.…”
Section: Table 33 Comparison Between Mri Estimates Of Regurgitant Vomentioning
confidence: 99%
“…Each FE model simulation consisted of both a passive diastolic filling phase and an active systolic contraction phase (LS-DYNA, Livermore Software Technology Corporation). The methods used in this study to create the finite element models and the equations used to drive the model simulations were obtained from previous research [33,37,27]. The passive myocardium response was represented using a nearly incompressible, transversely isotropic, hyperelastic material defined by the following strain energy function [13,14]:…”
Section: Finite Element Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…LV remodeling particularly occurs at the ischemic area and the region surrounds this area, 6‐8 which is also known as the border zone and has a unique form of dysfunctional myocardium that partly composed of normal cells and severely damaged ischemic cells 9,10 . The abnormal mechanics of the border zone is due to the fact that it contains normally perfused but hypocontractile myocardium.…”
Section: Introductionmentioning
confidence: 99%